ERPs While Judging Meaningfulness of Sentences With and Without Homonym or Morpheme Spelling Foils: Comparing 4th to 9th Graders With and Without Spelling Disabilities. Issue 4 (19th May 2017) - Richards, Todd; Pettet, Mark; Askren, Mary; Mestre, Zoé; Grabowski, Thomas; Yagle, Kevin; Wallis, Peter; Northey, Mary; Abbott, Robert; Berninger, Virginia
ABSTRACT: Thirteen students with and twelve students without spelling disabilities judged whether sentences (1/3 all correct spellings, 1/3 with homonym foil, 1/3 with morpheme foil) were meaningful while event-related potentials (ERPs) were measured with EGI Geodesic EEG System 300 (128-channel hydro-cell nets). For N400, Rapid Automatic Switching (RAS) correlated with comprehending sentences with homonym foils in control group but with morpheme foils in SLD group. For P600, dictated spelling correlated with comprehending sentences with morpheme foils in the control group but solving anagrams with homonym foils in the SLD group. Educational significance and neuropsychological significance of these contrasting results are discussed.